Writing for publication in nursing and healthcare : getting it right - Holland, Karen, 1949-; Watson, Roger, 1955- (John Wiley & Sons Ltd, 2021)
"Writing for Publication in Nursing and Healthcare helps readers develop the skills necessary for publishing in professional journals, presenting conference papers, authoring books, research reports, and literature reviews, and more. This comprehensive resource covers all aspects of writing for publication, including good practice in reviewing, the editorial process, ethical aspects of publishing, and the rules that govern academic writing, publishing, and dissemination. Assuming no prior expertise in the subject, the text uses an accessible, step-by-step approach that incorporates a wealth of real-life examples, hands-on activities, and valuable tips throughout. The second edition reflects the latest developments, guidelines, and practices both in academic publishing and in research assessment and dissemination. New and updated material covers the increasing use of social media to disseminate published work, post-publication scrutiny, contemporary issues surrounding predatory or unethical publishers, and new requirements for research registration and submission data. Edited by leading experts in the field, this practical how to guide: Describes the basics of writing for publication and how to get started. Includes numerous examples illustrating the practical ways abstracts, papers, book reviews, and other publications are written and disseminated. Discusses current issues and developments, such as the impact of major ethics organisations on publishing worldwide and the rise of online journals, blogging, and podcasting. Features contributions by internationally recognised academics and practitioners. Explains how to turn research reports and other assignments into publishable works. The definitive introduction to the subject, Writing for Publication in Nursing and Healthcare is a must-have for all nurses and healthcare professionals, as well as undergraduate and graduate students in nursing and healthcare programs who are required to write for publication.--